Financial Sector Assessment : Republic of Lithuania - World Bank (Washington, DC, 2013)
This Financial Sector Assessment (FSA) summarizes the key findings and recommendations of the 2007 Financial Sector Assessment Program (FSAP) update report for the Republic of Lithuania. The FSA, which focuses on developmental issues, should be read together with the Financial System Stability Assessment (FSSA) in order to get a full overview of the findings and recommendations of the 2007 Republic of Lithuania FSAP update. The FSAP update team noted progress since the 2002 banking sector vulnerability assessment, and evaluated regulatory and supervisory challenges for the banking and non-banking sectors; cross-border arrangements, safety nets, crisis management preparedness; the pension reform, and capital market development.